Aspects of Toxoplasma Infection on the Reproductive System of Experimentally Infected Rams (Ovis Aries) - Welber Daniel Zanetti Lopes; Alvimar José da Costa; Luis Fernando Santana; Ricardo Silva dos Santos; Walter Matheus Rossanese; Wilton Carlos Zanetti Lopes; Gustavo Henrique Nogueira Costa; Cláudio Alessandro Sakamoto; Thais Rabelo dos Santos (Journal of Parasitology Research)
Eight reproductive rams with no prior reproductive disease were distributed into three groups of infection with T. gondii: GI, 3 rams, 2.0×105 P strain oocysts; GII, 3 rams, 1.0×106 RH strain tachyzoites; GIII, 2 control rams. Clinical parameters were measured and serological evaluations (IIF) were performed. Presence of the parasite in the semen was investigated by PCR and bioassay techniques. The rams presented clinical alterations (hyperthermia and apathy) related to toxoplasmosis in both groups infected with Toxoplasma gondii. All the inoculated rams responded to antigenic stimulus, producing antibodies against T. gondii from postinoculation day 5 onwards. In ovine groups I and II, the greatest titers observed were 1 : 4096 and 1 : 8192, respectively. In semen samples collected from these two groups, the presence of T. gondii was detected by bioassay and PCR. This coccidian was isolated (bioassay and PCR) in tissue pools (testicles, epididymis, seminal vesicle, and prostrate) from two rams infected presenting oocysts and in one presenting tachyzoites.